Exenatide Delays the Progression of Nonalcoholic Fatty Liver Disease in C57BL/6 Mice, Which May Involve Inhibition of the NLRP3 Inflammasome through the Mitophagy Pathway. (15th April 2018) - Shao, Ning; Yu, Xin-Yang; Ma, Xue-Fei; Lin, Wen-Jian; Hao, Ming; Kuang, Hong-Yu
Abstract : Objective . This study is aimed at investigating whether exenatide (Exe) delays the progression of nonalcoholic fatty liver disease (NAFLD) in C57BL/6 mice by targeting the NLRP3 inflammasome through the autophagy/mitophagy pathway. Methods . Thirty male C57BL/6 mice were randomly divided into three groups: control group (n = 10 ), model group (n = 10 ), and Exe (exenatide) group (n = 10 ). Mouse models of NAFLD and diabetes were established using a high-fat diet and streptozocin. Results . The levels of fasting blood glucose (FBG), total cholesterol (TC), and triglyceride (TG) in the serum were significantly reduced after Exe treatment. The body weight, liver weight/body weight, and number of lipid droplets in the liver significantly decreased in Exe-treated mice. Treatment with Exe markedly reduced the levels of liver lipids, malondialdehyde (MDA), and alanine aminotransferase (ALT) in serum and livers. The number of autophagosomes increased significantly in the Exe group. The expression of LC3A/B-II/I, Beclin-1, Parkin, and BNIP3L increased significantly, whereas NLRP3 and IL-1 β proteins were suppressed after Exe treatment. Conclusion . We successfully established a mouse model of NAFLD and diabetes. Exe may reduce oxidative stress injury and inhibit the NLRP3 inflammasome by enhancing the autophagy/mitophagy pathway in liver, which has a protective effect on the liver in NAFLD and diabetes in C57BL/6 mice.